Incubating green turtle (Chelonia mydas) eggs at constant temperatures: Hatching success, hatchling morphology and post-hatch growth. (February 2022) - Yao, Yun-Tao; Du, Yu; Pan, Jia-Xin; Lin, Chi-Xian; Ji, Xiang; You, Wen-Hui
Abstract: Past studies applying constant-temperature incubation of eggs have involved all species of sea turtles, but rarely can we find a single one incubating eggs at three or more temperatures. Here, we incubated green turtle ( Chelonia mydas ) eggs from Ganquan Island, South China Sea, at five constant temperatures (26, 28, 30, 32 and 34 °C) to determine hatching success, incubation length and hatchling phenotype at each test temperature and temperatures optimal for embryonic development. Temperature affected hatching success, incubation length and all seven examined hatchlings traits, and clutch origin affected three (head length, fore-flipper length and hind-flipper length) of the seven. Hatching success was lowest at 34 °C and none of hatchlings hatched at this temperature was normal and survived over one week. The rate of embryonic development and the rate of post-hatch growth both were lowest at 26 °C. Given that low survival and growth rates can translate into reduced individual fitness, we conclude that both 26 °C and 34 °C are unsuitable for incubation of C. mydas eggs. Post-hatch growth was fastest in hatchlings incubated at 30 °C, and eggs of C. mydas incubated at temperatures around 30 °C are more likely to produce mixed sexes. Accordingly, we conclude that temperatures within the range from 28 °C to 32 °C are generally optimal for embryonic development of C. mydas . Graphical abstract: Image 1 Highlights: This study is the first to incubate green turtle eggs at up to five constant temperatures from 26–34 °C. Both the rate of embryonic development and the rate of post-hatch growth were lowest at 26 °C. Hatching success was lowest at 34 °C, with none of hatchlings hatched being normal nor surviving over one week. Temperature affected all examined variables, and clutch origin affected three hatchling morphological variables. Temperatures from 28–32 °C are optimal for embryonic development of C. mydas.